"Qui trop embrasse, mal étreint" ? Ambiguïtés et limites des politiques de diversité dans l'enseignement supérieur en France et en Espagne - Marie Carcassonne; Séverine Chauvel; Géraldine Farges; Leïla Frouillou; Carmen Marquez; Loïc Szerdahelyi; Elise Tenret (Les éditions de la Maison des sciences de l'Homme, 2023)
Based on a literature review conducted in France and Spain and sixteen interviews conducted in 2017 and 2018 in three French and two Spanish universities, this article questions diversity policies in higher education in a comparative perspective. First, the article shows the influence of American and European institutions on these policies, as well as their link with notions imported from corporate policies. A comparison of the criteria used in the various measures which aim at promoting diversity in universities in France and Spain highlights, in a second part, the fluctuating nature of diversity, with variations depending on the context or the target: students or staff. In fact, diversity policies in France seem to be more focused on the international or "diverse" character of the student body from a territorial point of view - or even indirectly from a migratory point of view; in Spain, disability is given a much more central place in the measures for the diversification of the public. When these policies are directed towards staff, they are essentially based on gender equality and attention to disability in both countries. Finally, the article examines the political stakes involved in maintaining the vagueness of this notion, by looking at how it is interpreted and put into practice by those in charge of diversity policies in universities.